Fibroblast growth factor 23 as a predictor of cardiovascular and all-cause mortality in prospective studies. (June 2017) - Qin, Zhexue; Liu, Xi; Song, Mingbao; Zhou, Quan; Yu, Jie; Zhou, Baoshang; Wu, Yazhou; He, Yongming; Huang, Lan
Abstract: Background and aims: The prognostic value of fibroblast growth factor 23 (FGF23) for mortality remains controversial. We performed a meta-analysis of cohort studies to examine the controversial relationship between FGF23 and mortality. Methods: PubMed, EMBASE, the Cochrane Library databases and reference bibliographies were searched through September 2016 to identify prospective cohort studies with relative risks (RRs) and 95% confidence intervals (CIs) for FGF23 and mortality. A random effects model was used to pool the risk estimates. A dose-response analysis of the risk for all-cause mortality associated with FGF23 was conducted using the generalized least squares trend estimation method. Results: Nineteen prospective cohort studies were eligible for inclusion in this meta-analysis, of which 16 reported all-cause mortality and 9 reported cardiovascular mortality. During the follow-up periods ranging from 1 to 18.6 years, 5606 deaths occurred among 22, 805 participants and 2458 cardiovascular deaths occurred among 28, 845 participants. Elevated FGF23 was associated with an increased risk of all-cause mortality (RR 1.68; 95% CI 1.48–1.92) and cardiovascular mortality (RR 1.68; 95% CI 1.38–2.04) with moderate heterogeneity. These associations were not markedly modified by the geographic location, follow-up length, patient predisposition, FGF23 measurement or study quality. A sensitivity analysis yielded a similar effect on the pooled risk estimate. Evidence of a nonlinear relationship between FGF23 and all-cause mortality was observed in the dose-response analysis, with the risk gradually increasing as FGF23 increased. Conclusions: This meta-analysis showed that individuals with increased plasma FGF23 levels might suffer a higher risk of all-cause mortality and cardiovascular mortality. Graphical abstract: Highlights: FGF23 is associated with an increased risk of future all-cause mortality. FGF23 is associated with an increased risk of future cardiovascular mortality. All-cause mortality risk gradually increases with an increase in FGF23 levels.